Aplikasi Deteksi Dini Plagiarism Penelitian Ilmiah Menggunakan Algoritma Consine Similarity Berbasis Web - Ahlun Nazar Fadhullah; Fauziah Fauziah; Winarsih Winarsih (KITA Institute, 2022)
Scientific Writing A graduation requirement for several students at each University. In making the Scientific Writing / Final Project, it is expected that final year students can make a journal/writing that is as original as possible and without plagiarism in order to meet innovation in society in the future to get a good and useful solution, especially in the IT field. The purpose of this study is to build a web-based application for early detection of plagiarism in scientific writing using the Cosine Similarity Algorithm method which will make it easier for students to determine the choice of final assignment title so that they can detect early plagiarism. The problem that often occurs in determining the title of scientific writing is not knowing about the previous titles that already exist, which often results in revisions at the beginning of the collection of outlines and journal titles. The method used is Cosine Similarity, this method is a method that can be used to calculate similarities between two objects. This calculation is based on the Vector Space Similarity Measure, namely, in calculating the level of similarity, the object will be expressed in vector form by using keywords as a measure.